Clinical case of pernicious anemia - V. Arhipenko (Clinical Medicine and Pharmacology, 2026)
Vitamin B12 - deficiency anemia (pernicious anemia, Addison-Biermer disease) – megaloblastic anemia, arising due to the deficiency of cyanocobalamin in the body, characterized by impaired erythropoiesis, damage to the hematopoietic tissue, digestive and nervous systems. Presented modern data on epidemiology, etiology, pathogenesis, diagnosis and treatment of vitamin B12-deficiency anemia based on clinical guidelines. Special attention is paid to the role of autoimmune mechanisms in the development of the disease and modern approaches to replacement therapy. As an illustration, a clinical case of pernicious anemia in a 68-year-old patient with damage to the nervous system is presented, demonstrating typical diagnostic errors and a successful response to pathogenetic therapy.